Nonlinear modular latin queen squares - Bell, Jordan (Utilitas Mathematica, 2007)
In this paper we give a new method for constructing non-linear modular Latin queen squares of order p for all prime p > 521. Modular Latin queen squares represent placements of n2 nonattacking queens on the n × n × n modular chessboard.